Cancer stem cell‐like characteristics and telomerase activity of the nasopharyngeal carcinoma radioresistant cell line CNE‐2R. (13th August 2018) - Chen, Kai‐Hua; Guo, Ya; Li, Ling; Qu, Song; Zhao, Wei; Lu, Qi‐Teng; Mo, Qi‐Yan; Yu, Bin‐Bin; Zhou, Lei; Lin, Guo‐Xiang; Sun, Yong‐Chu; Zhu, Xiao‐Dong
Abstract: The radioresistance of nasopharyngeal carcinoma (NPC) may be related to cancer stem cells (CSCs), and the characteristics of CSCs may be maintained by telomerase activity. In this study, we explored the CSC‐like characteristics and telomerase activity of the NPC radioresistant cell line CNE‐2R. This work provides a foundation for future studies on stem cell‐targeted therapies by targeting the radioresistance of NPC. The expression of stem cell‐related genes/proteins and the hTERT gene/protein in CNE‐2R and its parent radiosensitive cell line CNE‐2 were detected using qPCR/Western Blot. Label‐retaining cells (LRCs) were detected through immunocytochemistry, and telomerase activity was detected using a PCR‐ELISA kit. CD133 expression was detected with flow cytometry. CNE‐2R‐CD133+ and CNE‐2R‐CD133− cells were separated with magnetic‐activated cell sorting. The proliferation and tumorigenesis capacities of CNE‐2R‐CD133+, CNE‐2R‐CD133−, and CNE‐2R cells were compared with a CCK‐8 assay, sphere formation assay, and an in vivo experiment. Our results showed that the expression of stem cell‐related genes and the hTERT gene in CNE‐2R cells was higher than those in CNE‐2 cells. Similarly, the expression of stem cell‐related proteins and the hTERT protein in CNE‐2R cells was markedly higher than those in CNE‐2 cells. The proportion of LRCs in CNE‐2R and CNE‐2 cells was (3.10 ± 0.63%) vs (0.40 ± 0.35%; P < 0.001), respectively. Telomerase activity in CNE‐2R cells was remarkably higher than that in CNE‐2 cells. Flow cytometry suggested that the CD133 positive rates in CNE‐2R and CNE‐2 cells were (2.49 ± 0.56%) vs (0.76 ± 0.25%; P = 0.008), respectively. Meanwhile, the proliferation capacity, tumorigenesis capacity, and telomerase activity of CNE‐2R‐CD133+ cells were notably higher than those of CNE‐2R‐CD133− and CNE‐2R cells. Collectively, CNE‐2R displayed CSC‐like characteristics; our results also showed that CNE‐2R cells, especially the sorted CSCs, had high telomerase activity levels. Abstract : Our study initiatively explored the CSC‐like characteristics and telomerase activity of nasopharyngeal carcinoma radioresistant cells, as well as the correlation between the two, to provide a foundation for studies on CSCs targeted therapy for radioresistant nasopharyngeal carcinoma.